Kinesiotaping Versus Instrument Assisted Soft Tissue Mobilization on Upper Trapezius Myofascial Trigger Points: A Randomized Controlled Trial - Mesaed Mohamed, Reham Sayed; Amin, Fatma Sedeek; M. Hassan, Ibrahim (Journal of Neonatal Surgery, 2025)
Background: Myofascial trigger points (MTrPs) are hypersensitive nodules of contracture that are palpable to affected muscles and produce localized pain in and around the affected muscle or trigger distant referred pain. Objective: This study was designed to investigate the effects of Instrument assisted soft tissue mobilization versus kinesiotaping on upper trapezius myofascial trigger points. Methods: fifty subjects with active trigger points at both side (38 females and 13 males) were divided randomly into three equal groups. Group "A" received traditional therapy three times/week while group "B" received KinesioTaping twice/week for four weeks. Group "C" received Instrument Assissted Soft Tissue Mobilization three times/week. Visual analogue scale, Pressure pain threshold, Cervical range of motion and Arabic neck disability index were used to evaluate subjects at two intervals (pre-treatment and post-treatment). Results: Statistical analysis shown that there was a significant change within-group of all variables pre-post treatment at groups A, B and C as (p<0.05). Between-group analysis there was no significant change in pre value of all variables as (p>0.05) while post-treatment there was a significant change in all variables as (p<0.05). Conclusion: Instrument assisted soft tissue mobilization and kinesiotaping are most effective methods in the management of subjects with active trigger points at upper trapezius myofascial trigger points with superiority for Instrument assisted soft tissue mobilization.